2022
DOI: 10.3390/foods11223558
|View full text |Cite
|
Sign up to set email alerts
|

Plant Antioxidants in Dry Fermented Meat Products with a Healthier Lipid Profile

Abstract: Consumers’ perception of meat products has changed in recent years, which has led to an increased interest in healthier meat products. In response to this demand, academia and industry have made efforts to reformulate meat products, especially dry fermented meat products, which are known for their high fat contents, mainly saturated fat. The use of plant or marine oils stabilized in emulsion gels (EGs) or oil-bulking agents (OBAs) as animal fat replacers has been one of the most advantageous strategies to refo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Moreover, they take more time to be digested in the stomach Foods 2024, 13, 304 2 of 17 than proteins or carbohydrates, delaying the feeling of hunger. Fats not only supply energy but also serve as the precursors of glycolipids and phospholipids, two crucial components in cell membranes [3]. Several research studies have shown a correlation between the consumption of animal fats in a balanced diet and a lower incidence of cardiovascular illnesses and related risk factors, including obesity, insulin resistance, and tumours [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they take more time to be digested in the stomach Foods 2024, 13, 304 2 of 17 than proteins or carbohydrates, delaying the feeling of hunger. Fats not only supply energy but also serve as the precursors of glycolipids and phospholipids, two crucial components in cell membranes [3]. Several research studies have shown a correlation between the consumption of animal fats in a balanced diet and a lower incidence of cardiovascular illnesses and related risk factors, including obesity, insulin resistance, and tumours [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the applications of the oil-in-water emulsions are limited in food systems due to physical instability, soft texture and oxidation problems [ 7 ]. To overcome these problems, several strategies have been developed, including the utilization of proteins (soy proteins, sodium caseinate, whey proteins, corn germ protein), carbohydrates (starches, konjac glucomannan, cellulose, inulin, oat fiber, polysaccharide), hydrocolloids (xanthan, locust bean gum) and even natural antioxidants (curcumin, carotenes, annatto bixin, capsorubin) [ 8 , 9 , 10 ]. Zhang et al [ 11 ] used water-soluble β-glucan to make low-fat sausages with the presence of peanut protein isolate or soy protein isolate, which significantly improved the water-holding capability and increased the hardness, chewiness and cohesiveness of prepared sausages.…”
Section: Introductionmentioning
confidence: 99%